SOCIAL GUIDANCE FOR GROUPS OF DRUG ADDICT CLIENTS USING BEHAVIORAL THEORY AT THE CLASS II PEKALONGAN CORRECTIONAL CENTER - Pamungkas, Andika Putra; Equatora, Muhammad Ali (Journal of Management Small and Medium Enterprises (SMEs), 2025)
Basically, drugs have three characteristics which can then influence users in terms of consuming drugs where a person will be reminded and will be more influenced by the tendency to consume drugs further, namely related to tolerance where the more a person becomes one with the presence of drugs where in the end the dose of users are so high that they will be influenced by tendencies. The aim of this research is to determine the implementation of social guidance for drug addict client groups using behavioral theory at the Pekalongan Class II Correctional Center. In this research, the research design used is a case study. A case study is a research design in which many areas related to evaluation are found in the research, where the research develops a more in-depth analysis related to cases of program events, process activities. The results and discussion of this research are based on behavioristic theory and group social guidance, namely the Implementation of Group Social Guidance for Drug Addict Clients Using Behavioral Theory at the Class II Pekalongan Correctional Center, a program that has been implemented to fulfill clients' rights to receive guidance after serving a criminal term. Social Guidance for Groups of Drug Addict Clients Using Behavioral Theory is a form of guidance in the Class II Pekalongan Bapas where the result of this guidance is that it can reduce addiction and recidivism rates in the Pekalongan Class II Bapas itself. The usual program is community-based group guidance. Keywords: Narcotics; Prisons; Correctional Clients; Guidance